1993
DOI: 10.1128/mcb.13.1.649
|View full text |Cite
|
Sign up to set email alerts
|

The REB1 site is an essential component of a terminator for RNA polymerase I in Saccharomyces cerevisiae.

Abstract: We have identified a terminator for transcription by RNA polymerase I in the genes coding for rRNA of the yeast Saccharomyces cerevisiae. The terminator is located 108 bp downstream of the 3' end of the mature 25S rRNA and shares several characteristics with previously studied polymerase I terminators in the vertebrates.For example, the yeast terminator is orientation dependent, is inhibited by its own sequence, and forms RNA 3' ends 17 2 bp upstream of an essential protein binding site. The recognition sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 33 publications
3
100
2
Order By: Relevance
“…The effects of the depletion or absence of Rnt1p on other pre-rRNA processing reactions were assessed by Northern hybridization (Fig+ 4)+ In general, the same defects were observed in the GAL::rnt1 strain following transfer to glucose medium and in the rnt1-⌬ strain+ The phenotypes were, however, more marked in the rnt1-⌬ strains that completely lack Rnt1p+ The lower levels of pre-rRNAs seen in the strains grown in RSG medium (Fig+ 4, lanes 1 and 3) are due to the effects of nutritional shift down on pre-rRNA transcription+ Rnt1p was reported to cleave the pre-rRNA in the 39 ETS (Abou Elela et al+, 1996)+ Consistent with this, we detect 39 extended forms of pre-rRNA species that normally terminate at the 39 ETS (35S, 27SA, and 27SB) as well as the 25S rRNA+ The extended species are indicated as 35S*, 32S*, 27SA* 2 , 27SB*, and 25S* (see also Probe 022, hybridizing across the 25S rRNA/39 ETS junction, did not give a stronger signal than probe 053 (data not shown), indicating that the major transcripts in the rnt1-⌬ mutants terminate between ϩ180 and ϩ264+ This suggests that they terminate at site T2 (position ϩ210) (Veldman et al+, 1980;Kempers-Veenstra et al+, 1986;van der Sande et al+, 1989) rather than the termination site identified in vitro at ϩ108, close to the Reb1p binding site (Lang & Reeder, 1993)+ Much lower levels of the larger 35S** RNA were detected with oligo 054 in the rnt1-⌬ strain (note that the exposure of the Northern shown in Fig+ 4, row I, was 2+5-fold longer than that shown in Fig+ 4, row II)+ 35S** extends beyond ϩ210, most likely because of read-through of T2, possibly to termination site T3A at ϩ690 (van der Sande et al+, 1989)+ For reasons that are not clear, the ratio of 35S** to 35S* is higher in the GAL::rnt1 strain than in the rnt1-⌬ strain+ The larger species marked * (Fig+ 4, row I) has not been further characterized, but it may extend through the nontranscribed spacer region to termination site Tp, reported to lie 300 nt upstream of the next rDNA transcription unit (van der Sande et al+, 1989)+ We conclude that pre-rRNA transcription normally terminates in the 39 ETS between ϩ180 and ϩ264 (most probably at ϩ210) with lower levels of read-through transcripts+ These species are presumably not detected in wild-type cells because Rnt1p cleaves the nascent pre-rRNAs cotranscriptionally+ The 25S* rRNA was underaccumulated in both the GAL::rnt1 strain grown on glucose medium and in the rnt1-⌬ strains (Fig+ 4, row VII), compared to the 25S rRNA in wild-type strains+ The level of the 27SB* prerRNA (Fig+ 4, row V) was also reduced compared to the wild-type species, indicating that synthesis of the 25S rRNA is inhibited in the strains lacking Rnt1p+ The 20S and 27SA 2 pre-rRNAs are both generated by cleavage at site A 2 (see Fig+ 1B)+ In the rnt1-⌬ strains, the 27SA* 2 (Fig+ 4, row IV) is not, however, reduced as much as 20S* (Fig+ 4, row IX), indicating that processing of 27SA* 2 to 27SB* is delayed+ In the absence of Rnt1p, the 39 extended pre-rRNAs therefore appear to be inefficiently processed+…”
Section: Rnt1p Is Required For Processing In the 39 Etsmentioning
confidence: 96%
“…The effects of the depletion or absence of Rnt1p on other pre-rRNA processing reactions were assessed by Northern hybridization (Fig+ 4)+ In general, the same defects were observed in the GAL::rnt1 strain following transfer to glucose medium and in the rnt1-⌬ strain+ The phenotypes were, however, more marked in the rnt1-⌬ strains that completely lack Rnt1p+ The lower levels of pre-rRNAs seen in the strains grown in RSG medium (Fig+ 4, lanes 1 and 3) are due to the effects of nutritional shift down on pre-rRNA transcription+ Rnt1p was reported to cleave the pre-rRNA in the 39 ETS (Abou Elela et al+, 1996)+ Consistent with this, we detect 39 extended forms of pre-rRNA species that normally terminate at the 39 ETS (35S, 27SA, and 27SB) as well as the 25S rRNA+ The extended species are indicated as 35S*, 32S*, 27SA* 2 , 27SB*, and 25S* (see also Probe 022, hybridizing across the 25S rRNA/39 ETS junction, did not give a stronger signal than probe 053 (data not shown), indicating that the major transcripts in the rnt1-⌬ mutants terminate between ϩ180 and ϩ264+ This suggests that they terminate at site T2 (position ϩ210) (Veldman et al+, 1980;Kempers-Veenstra et al+, 1986;van der Sande et al+, 1989) rather than the termination site identified in vitro at ϩ108, close to the Reb1p binding site (Lang & Reeder, 1993)+ Much lower levels of the larger 35S** RNA were detected with oligo 054 in the rnt1-⌬ strain (note that the exposure of the Northern shown in Fig+ 4, row I, was 2+5-fold longer than that shown in Fig+ 4, row II)+ 35S** extends beyond ϩ210, most likely because of read-through of T2, possibly to termination site T3A at ϩ690 (van der Sande et al+, 1989)+ For reasons that are not clear, the ratio of 35S** to 35S* is higher in the GAL::rnt1 strain than in the rnt1-⌬ strain+ The larger species marked * (Fig+ 4, row I) has not been further characterized, but it may extend through the nontranscribed spacer region to termination site Tp, reported to lie 300 nt upstream of the next rDNA transcription unit (van der Sande et al+, 1989)+ We conclude that pre-rRNA transcription normally terminates in the 39 ETS between ϩ180 and ϩ264 (most probably at ϩ210) with lower levels of read-through transcripts+ These species are presumably not detected in wild-type cells because Rnt1p cleaves the nascent pre-rRNAs cotranscriptionally+ The 25S* rRNA was underaccumulated in both the GAL::rnt1 strain grown on glucose medium and in the rnt1-⌬ strains (Fig+ 4, row VII), compared to the 25S rRNA in wild-type strains+ The level of the 27SB* prerRNA (Fig+ 4, row V) was also reduced compared to the wild-type species, indicating that synthesis of the 25S rRNA is inhibited in the strains lacking Rnt1p+ The 20S and 27SA 2 pre-rRNAs are both generated by cleavage at site A 2 (see Fig+ 1B)+ In the rnt1-⌬ strains, the 27SA* 2 (Fig+ 4, row IV) is not, however, reduced as much as 20S* (Fig+ 4, row IX), indicating that processing of 27SA* 2 to 27SB* is delayed+ In the absence of Rnt1p, the 39 extended pre-rRNAs therefore appear to be inefficiently processed+…”
Section: Rnt1p Is Required For Processing In the 39 Etsmentioning
confidence: 96%
“…In yeast, just as in mammals and frogs, poll does not terminate at the 3' end of the mature 25S RNA but continues on for 100-200 bp (Yip and Holland, 1989;van der Sande et ai, 1989;Lang and Reeder, 1993). Current literature presents two different schools of thought concerning exactly where it does terminate.…”
Section: Termination In Yeastmentioning
confidence: 99%
“…Involvement of the Rebip-binding site was determined by studying a set of point mutants in which the ability to bind Rebip in a gel shift assay correlated exactly with the ability to direct RNA 3' end formation in the transcription assay (Lang and Reeder, 1993). This included one mutant which simultaneously increased both the binding affinity for Reb1P and the efficiency of RNA 3' end fonnation.…”
Section: Termination In Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety percent of yeast RNAPI terminates at the first terminator (T1), situated upstream of a pause-inducing factor-binding site that is recognized in vitro by Reb1 (Ju et al 1990;Lang and Reeder 1995). In mammals, the major terminator, called the Sal box (Grummt et al 1985;Kuhn et al 1988), is recognized by TTF-I (transcription termination factor for polI) , and like the Reb1-binding site, it must be correctly oriented to cause termination (Grummt et al 1985;Lang and Reeder 1993). The mouse Sal box is an 18-bp element repeated 10 times in the IGS, while humans contain a shorter Sal box (11 bp) that is recognized by the human TTF-I (Bartsch et al 1987;Pfleiderer et al 1990;.…”
Section: Rnapi Terminationmentioning
confidence: 99%